Serum electrolyte changes in major surgical trauma - Singh, Ram Ranjan; Shekhar, Sudhanshu; Akhtar, Md. Jawed; Shankar, Vijay (International Journal of Research in Medical Sciences, 2017)
Background:Operative trauma is followed by a series of changes collectively referred to as metabolic response to injury, the magnitude and duration of the response being directly proportional to the severity of the trauma. Operative trauma imposes a great impact in the physiology of fluid and electrolytes within the body. Fluid and electrolyte management has thus been an integral part of care of each and every surgical patient. In the present study, an attempt has been made to study the electrolyte changes, especially that of sodium and potassium following surgical trauma due to various surgical procedures and its implication in the principles of replacement therapy. Methods: The present study is being carried out in 50 surgical patients both male and female, of age group of 18-70 years. Serum electrolytes (Na, K, Cl, Ca and Mg) of each patient was estimated one day before operation (-1), on the day of operation (0) after surgery, next consecutive 4 postoperative days (+1, +2, +3, +4) and on 7th postoperative day (+7). Results: There occur a fall in serum sodium and chloride level on the day of operation in all cases which attain a still lower level in 1st postoperative day. Then from 2nd postoperative day onwards, there occur a gradual rise and attain preoperative value by 4th postoperative day in most cases and by 7th postoperative day in all cases. There occurs an elevation on serum potassium level from the day of operation, which becomes highest in 1st postoperative day. This follows a gradual fall in from 2nd postoperative day onwards and attains preoperative level in most cases by 4th postoperative day and in all cases by 7th postoperative day. Serum calcium and serum magnesium showed a constant serum level throughout the study period. Conclusion: There was tendency of the body to conserve sodium, chloride on the day of operation and on 1st postoperative day, while potassium is excreted from body in these days. From postoperative day onwards the trend started to attain preoperative values and completed by day 4 postoperatively. The changes in serum electrolytes were directly proportional to degree of tissue trauma or tissue handling.